PROCESSING OF CHURCH PUMP JUICE TO REDUCE HYPERTENSION IN THE ELDERLY IN THE WORK AREA OF SITA MANGGARAI PUSKESMAS EAST - Hepilita, Yohana; Dewiyanti Wea, Lidwina; Fariday Dewi, Claudia; Suryati, Yuliana; Yuniati Demang, Fransiska; Suyen Ningsih, Oliva; Getrida Simon, Maria; Handi, Heri bertus (LPPM Univ. Ibn Khaldun Bogor, 2022)
Lecturer community service program with the theme. Processing of Siamese Pumpkin Juice to Reduce Hypertension in the Elderly in the Work Area of ​​the Sita Health Center, East Manggrai Regency. Hypertension is persistent blood pressure where the systolic pressure is 140 mmHg and the diastolic pressure is 90 mmHg, based on two or more measurements and checked every 5 minutes. Chayote is a subtropical plant and belongs to the cucurbitaceus species which is often used as food. The benefits of potassium, alkaloids, and flavonoids in chayote can reduce blood pressure. The purpose of the Lecturer's community service activities is to use chayote to be processed into juice that is beneficial for health, especially to reduce high blood pressure/hypertension in the elderly in the work area of ​​the Sita Health Center. the number of elderly at the Sita Health Center is 120 people and 90 people have hypertension and 6 of them have a stroke due to hypertension, because of the above problems the nursing study program lecturer team held community service activities by processing pumpkin syam into juice to reduce hypertension in the elderly because pumpkin juice Siamese affects reducing blood pressure in hypertensive patients. Patients with hypertension are expected to apply more ways to overcome hypertension by consuming herbal medicines such as chayote because it has many benefits and the price is cheap, and it is also easy to obtain.